Qualifying software engineers undergraduates in DevOps - challenges of introducing technical and non-technical concepts in a project-oriented course - Alves, Isaque; Rocha, Carla (2021 IEEE/ACM 43rd International Conference on Software Engineering: Software Engineering Education and Training (ICSE-SEET), 2021)
The constant changes in the software industry, practices, and methodologies impose challenges to teaching and learning current software engineering concepts and skills. DevOps is particularly challenging because it covers technical concepts, such as pipeline automation, and non-technical ones, such as team roles and project management. The present study investigates a course setup to introduce these concepts to software engineering undergraduates. We designed the course by employing coding to associate DevOps concepts to Agile, Lean, and Open source practices and tools. We present the main aspects of this project-oriented DevOps course, with 240 students enrolled it since its first offering in 2016. We conducted an empirical study, with both a quantitative and qualitative analysis, to evaluate this project-oriented course setup. We collected the data from the projects repository and students' perceptions from a questionnaire. We mined 148 repositories (corresponding to 72 projects) and obtained 86 valid responses to the questionnaire. We also mapped the concepts which are more challenging to students learn from experience. The results evidence that first-hand experience facilitates the comprehension of DevOps concepts and enriches classes discussions. we present a set of lessons learned, which may help professors better design and conduct project-oriented courses to cover DevOps concepts.